Newborn Neurobehavior Is Related to Later Neurodevelopment and Social Cognition Skills in Extremely Preterm-Born Children: A Prospective Longitudinal Cohort Study - Aho, Leena; Metsäranta, Marjo; Lönnberg, Piia; Wolford, Elina; Lano, Aulikki (Frontiers in Psychology, 2021)
Objective To evaluate the ability of the neonatal neurobehavioral characteristics to act as an indicator of later neurodevelopment and neurocognitive performance. Study design Sixty-six infants born extremely preterm (< 28 gestational weeks) were followed until 6.5 years. Neurobehavior at term age was assessed by the behavior subscale of the Hammersmith Neonatal Neurological Examination (HHNE) using dichotomic rating, optimal and non-optimal. The Griffiths Scales (GMDS) at two years, and Wechsler Intelligence Scales and a Neuropsychological Assessment at 6.5 years were used to assess neurodevelopment and neurocognitive performance including social cognition skills. Results An optimal auditory orientation at term age was associated with better developmental quotients (DQ) in Personal-Social, and Hearing-Language GMDS subscale at 2 years (p<0.05). An optimal visual alertness was associated with better Total (p<0.01), Locomotor (p<0.001), and Eye-Hand Coordination DQs (p<0.01) at 2 years, and with sensorimotor function (p<0.001), and social perception (p<0.01) tests at 6.5 years of age. Conclusion Newborn neurobehavior might serve as a precursor of social cognition skills and the HNNE behavior subscale offer a tool to identify infants at risk for later deficits in neurodevelopment and social cognition.